Essays on strategic voting - Mendes, T (2010)
In this thesis we extend the study of strategic voting to two frameworks that are novel to the literature. First, by analysing a four-party competition with purely instrumentally motivated voters (Part I); second, by focusing on a three-party competition where voters have instrumental and expressive motivations (Part II). We aim to explore an existing gap in the literature and, in particular, to investigate the possibility of a voting equilibrium with partial strategic voting and its stability. The three sub-models studied in Part I (including essay 1) and the model in Part II (including essays 2, 3 and 4) focus on the case of large electorates and include public uncertainty. This distinguishes them from Cox (1997), where no real uncertainty exists as the electorate gets large, and Myatt (2006), which includes both public and private information. Essays 2 and 3 present and explore the theoretical framework and implications for the model chosen for Part II and essay 4 applies it to the 1997 UK General Election. From essay 1 we obtain the result that in a single-ballot simple-plurality election there is a tendency towards the Duvergerian equilibrium in a four-party model. Also, an equilibrium with partial strategic voting is never stable. From essays 2 and 3 three main results arise: a Duvergerian equilibrium is never possible; a stable equilibrium always exists; and more information leads to less strategic voting – contrary to Myatt (2006). Both the impossibility of any Duvergerian equilibrium and the possibility of a stable interior equilibrium in multiple cases are central to our theory of voting that includes an expressiveness component. The simulations in essay 4 suggest that a very low level of expressiveness is needed to obtain a level of strategic voting compatible with the findings in Fisher (2004). The theory predicts the impossibility of some constituency results that are in fact frequently observed in British elections. Cox (1997), Making Votes Count. Cambridge, Cambridge University Press. Fisher (2004), ), Definition and Measurement of Tactical Voting: the Role of Rational Choice, British Journal of Political Science, 34(1), 152-66. Myatt (2006), On the Theory of Strategic Voting, Review of Economics Studies, Blackwell Publishing vol. 74(1), pages 255-281.